1994
DOI: 10.1038/bjc.1994.260
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for cervicography in the detection of premalignant lesions of the cervix uteri?

Abstract: S_nmary The characteristics of cervicography and the Papamncolaou smear test have been compared for the detection of cervix lesions classified as CIN I or more. A total of 4,015 women were entered into the study. (IARC, 1986;Laara et al., 1987;Day, 1989).Cervicography as a means of screening was introduced by Stafl at the beginning of the 1980s (Stafl, 1981 Screening results qualified as 'atypical' or 'trivial change' were considered to be negative tests. CIN I lesions were considered to be low-grade lesions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Coibion et al reported 99.1% specificity for cervicography (33), and we found 89.8% in the present study (Table IV). Among single screening methods, cervicography showed the highest sensitivity (94.3%, Table VI), which was improved significantly when combined with cervical cytology (98.1%, Table VI).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Coibion et al reported 99.1% specificity for cervicography (33), and we found 89.8% in the present study (Table IV). Among single screening methods, cervicography showed the highest sensitivity (94.3%, Table VI), which was improved significantly when combined with cervical cytology (98.1%, Table VI).…”
Section: Discussionsupporting
confidence: 75%
“…Based on recent active molecular biologic studies, many methods of classifying HPV infection and subtypes have been proposed, but the actual application of these methods is limited in actual clinical settings due to their sensitivity and specificity. The recently developed Hybrid Capture System is a non-amplified method and molecular hybridization method, which uses the chemiluminescent characteristic of DNA from smeared cervical cells, to easily determine the presence of HPV, and to distinguish the identified HPV into high-risk subtypes (HPV 16,18,31,33,35,45, 51, 52 and 56) or low-risk subtypes (HPV 6, 11, 42, 43 and 44) quantitatively (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervicography is a technique allowing visual examination of the external part of the cervix in large series of women. During a study to evaluate the relevance of cervicography to screening (Coibion et al, 1994), we used this technique to explore how the location of the transformation zone influenced the detection of premalignant lesions of the cervix.…”
mentioning
confidence: 99%
“…One of them is cervicography, which is popular in the USA and in some screening clinics in Europe. Although numerous groups have published results on screening with cervicography, wellconducted studies to evaluate cervicography (as compared to cytology) are rare [21]. The principal findings of these studies are that cytology and cervicography detect different pre-malignant lesions of the cervix.…”
Section: Cervical Cancermentioning
confidence: 99%